The Impact Implementation Of Relationship Marketing And Company Reputation On Concumer Trust In Sharia Paownshop Kutai Kartanegara Regency - Sabran Sabran; Devi Fuspita Sari; Raudatul Adawiyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract The purpose of this research is to know and examine the influence of relationship marketing and company reputation on consumer trust in Sharia Pawnshop Unit Kutai Kartanegara. Based on the reality as far as the researchers see marketing strategy that has been implemented the Sharia Pawnshop Unit Kutai Kartanegara has not produced maximum results, where the number of customers since 2017 until now in each month began to decline and began to rarely come or move using other similar business services. This study used quantitative data obtained from questionnaire data. The number of research samples as many as 45 people with the method of taking by saturated sampling. The analysis tool used multiple linear regression. Studies have found that 1. Relationship marketing and company reputation are simultaneously affecting on consumer trust, 2. Relationship marketing has a positive effect on consumer trust, 3. Company reputation has a positive effect on consumer trust, 4. The most dominant variable is relationship marketing. Keywords: Relationship marketing, company reputation, trust.